2022
DOI: 10.7759/cureus.24693
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal Sympathetic Hyperactivity After Traumatic Brain Injury: What Is Important to Know?

Abstract: Traumatic brain injury (TBI) is one of the leading causes of morbidity and mortality. The etiologies of TBI are varied and its complications can lead to paroxysmal sympathetic hyperactivity that was first described as a "sympathetic storm" or "diencephalic autonomic seizure." The clinical manifestations are rapid and sudden onset of sympathetic hyperactivity characterized by tachycardia, systolic hypertension, hyperthermia, tachypnea, and diaphoresis, all summarized in the latest and most accepted diagnostic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Accumulating studies confirmed that overwhelming sympathetic hyperactivity following brain injury impairs prognosis. [11][12][13] Moreover, β adrenergic blockers, targeting the sympathetic nervous system, reduced mortality of traumatic brain injury (TBI) by decreasing TBI-related catecholamine surge. [14,15] In short, it is reasonable to speculate that sympathetic nervous system controlled by β blockers might be an optional remedy to ameliorate survival for PBH.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating studies confirmed that overwhelming sympathetic hyperactivity following brain injury impairs prognosis. [11][12][13] Moreover, β adrenergic blockers, targeting the sympathetic nervous system, reduced mortality of traumatic brain injury (TBI) by decreasing TBI-related catecholamine surge. [14,15] In short, it is reasonable to speculate that sympathetic nervous system controlled by β blockers might be an optional remedy to ameliorate survival for PBH.…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms also affect adipose tissue, leading to lipolysis and the release of cytokines and adipokines. [70][71][72] The central mechanism of sympathetic activation is still poorly understood, but is probably driven by a loss of inhibitory control over excitatory autonomic centers. 73 Figure 3 illustrates how, in these situations of sympathetic hyperactivity, serum S100B levels rise at the expense of central and peripheral secretion.…”
Section: Does the Increase In S100b In The Csf Imply An Increase In S...mentioning
confidence: 99%
“…У 2010 році був затверджений термін ПСГ. Крім того, встановлено визначення та критерії діагностики: ускладнення різноманітних гострих уражень головного мозку незалежно від причини (травматичної чи іншої), що призводять до порушення центральної регуляції вегетативної функції, таким чином виключаючи клінічні синдроми з парасимпатичним компонентом [1].…”
Section: вступunclassified